Current status and clinical applications of tissue engineering of the gastrointestinal tract: a systematized narrative review - Liu, Yilin; Chong, Lynn; Read, Matthew (Frontiers in Gastroenterology, 2023)
Background: Since the advent of regenerative medicine, tissue engineering of the gastrointestinal tract (GIT) has been extensively studied in laboratory animals and humans to repair or reconstruct different GIT defects. Achievements in this field have led to novel approaches in curing GIT diseases circumventing morbid complications of current therapy.Objective: This review aims to describe recent advances in GIT tissue engineering with an emphasis on technologies closer to clinical translation.A literature search was conducted in Ovid MEDLINE ® ALL for relevant studies (2000 -Sep 2023) using the keywords 'tissue-engineering', 'scaffolds', 'organoids', 'cell-therapy', and 'gastrointestinal tract'. Articles were included if they were in vivo animal studies or clinical studies that investigated tissue engineering for treating GIT defects.Results: 48 articles were included in the final review. Many studies on esophageal defects thus far have described the success of covering partial-thickness defects with autologous cell sheets and closing fullthickness defects with decellularised scaffolds in both animals and humans. Limited reports have also demonstrated de novo organogenesis of the esophagus to repair short-segment circumferential esophageal defects with autologous pluripotent cells and scaffolds. In the stomach, multiple animal studies reported the feasibility of gastric epithelium regeneration using multipotent cells and/or scaffolds to correct partialthickness and full-thickness defects. One study observed the regeneration of whole-layer stomach defects using the organoids-on-polymer approach. Similarly, in the intestine, pluripotent cells and scaffolds were shown to effectively repair both partial-thickness and full-thickness defects. Animal experiments have produced tissue-engineered small intestines (TESI) with the organoids-on-polymer approach. Furthermore, in the rectum and anus, mesenchymal stem cell therapies with or without biosaffolds have shown promise for treating full-thickness defects in multiple human trials.Tissue-engineering approaches for repairing various types of GI defects in the esophagus, stomach, intestines, rectum and anus have been extensively explored in animal models, with promising outcomes. Moreover, successful human trials have demonstrated the feasibility of reconstructing esophageal, rectal and anal defects using these innovative approaches. Technologies such as stem cells, decellularization, organoids, and cell sheets are the most promising and closer to clinical translation. Collaboration between gastrointestinal surgery and regenerative medicine is expected to bring novel therapeutic modalities in the future.